Loss aversion and rent-seeking: An experimental study - Xiaojing Kong (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2008)
We report an experiment designed to evaluate the impact of loss aversion on rent-seeking contests. We find, as theoretically predicted, a negative relationship between rent-seeking expenditures and loss aversion. However, for any degree of loss aversion, levels of rent-seeking expenditure are higher than predicted. Moreover, we find that the effect of loss aversion becomes weaker with repetition of the contest.
Keywords: 330; Rent Seeking; Verlust; Risikoaversion; Verhaltensökonomik; Test